Enhancing Listening Comprehension Skill Through Research-based Learning of Vocational High School Students - Yessy Triasepta Hudiati; Sulistyani Sulistyani (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
This study aims to analyze the effect of Research-based Learning on Vocational High School students’ listening comprehension. This research is an experimental research that uses a quantitative approach, which is carried out using one group pre-test and post-test design. The research was held in Vocational High School PGRI 2 Kediri. The researcher takes class X Culinary 3 which was participated by 20 students as the sample with purposive reason. After the research was conducted, the following results were found: In the pre-test, students get an average score of 60.30. The average score increases in the post-test result to 70.50. Meanwhile, the result of the hypothesis test using t-test showed the result of sig(2-tailed) 0.04<0.05. From the result of the data, it can be concluded that Research-Based Learning can be applied in Vocational High School to improve students listening comprehension, especially in Vocational High School PGRI 2 Kediri